Shear Stress Promotes Arterial Endothelium-Oriented Differentiation of Mouse-Induced Pluripotent Stem Cells - Yan Huang; Xiaofang Chen; Jifei Che; Qi Zhan; Jing Ji; Yubo Fan (Stem Cells International)
Establishment of a functional vascular network, which is required in tissue repair and regeneration, needs large-scale production of specific arterial or venous endothelial cells (ECs) from stem cells. Previous in vitro studies by us and others revealed that shear stress induces EC differentiation of bone marrow-derived mesenchymal stem cells and embryonic stem cells. In this study, we focused on the impact of different magnitudes of shear stress on the differentiation of mouse-induced pluripotent stem cells (iPSCs) towards arterial or venous ECs. When iPSCs were exposed to shear stress (5, 10, and 15 dyne/cm2) with 50 ng/mL vascular endothelial growth factor and 10 ng/mL fibroblast growth factor, the expression levels of the general EC markers and the arterial markers increased, and the stress amplitude of 10 dyne/cm2 could be regarded as a proper promoter, whereas the venous and lymphatic markers had little or no expression. Further, shear stress caused cells to align parallel to the direction of the flow, induced cells forming functional tubes, and increased the secretion of nitric oxide. In addition, Notch1 was significantly upregulated, and the Notch ligand Delta-like 4 was activated in response to shear stress, while inhibition of Notch signaling by DAPT remarkably abolished the shear stress-induced arterial epithelium differentiation. Taken together, our results indicate that exposure to appropriate shear stress facilitated the differentiation of mouse iPSCs towards arterial ECs via Notch signaling pathways, which have potential applications for both disease modeling and regenerative medicine.